Aptamers and Cancer - Yazdanpanahi, Nasrin; Hashemi, Mehrdad; Movafagh, Abolfazl (Asian Pacific Journal of Cancer Biology, 2016)
Oligonucleotides Aptamers are single strands of DNA and RNA with the length of 20-100 nucleotides or peptides and unique three dimensional structure that is affected by nucleotide sequence. The structure exclusively influences aptamers’ bindings with its target molecule. It reduces performance or inactivate protein and this feature is used for therapeutic purposes. In addition and through connecting to signature molecule, aptamers are used to detect specific proteins. High efficiency of aptamer technology makes them a valuable tool for diagnosing and treating different diseases including cancer. The present study is an attempt to review recent studies in this field.